(untitled) (Hong Kong Journal of Ophthalmology, 2007)
Aim: To assess any difference in pain between sub- conjunctival injection of gentamicin and cefuroxime for cataract surgery. Patients and methods: This was a prospective single- blind clinical trial of 58 patients who underwent un- eventful cataract surgery under regional or topical anesthesia. They were given a subconjunctival injection of either gentamicin or cefuroxime at the end of surgery. All patients completed questionnaires on the degree of pain immediately after the injection and 10 minutes after the injection. The data were analyzed using Fischer’s exact test. Results: Comparison of the pain scores between the gentamicin group and cefuroxime group resulted in no significant differences in pain immediately after the injection and 10 minutes after the injection. There were no significant differences to the type of anesthetic. Conclusion: As there were no significant differences in pain following subconjunctival injection with gentamicin or cefuroxime, either antibiotic could be selected for endophthalmitis prophylaxis for cataract surgery.